An evaluation of wheelchair basketball players` nutritional status and nutritional knowledge levels - Eskici, G.; Ersoy, G. (The Journal of Sports Medicine and Physical Fitness, 2016)
Aim: This study aims to assess the nutritional status of women paralympic athletes and their nutritional knowledge.